Biomimetic drug nanocarriers prepared by miniemulsion polymerization for near-infrared imaging and photothermal therapy. (15th January 2016) - Han, Haijie; Zhang, Shimiao; Wang, Yin; Chen, Tingting; Jin, Qiao; Chen, Yangjun; Li, Zuhong; Ji, Jian
Abstract: Miniemulsion reversible addition-fragmentation chain transfer (RAFT) polymerization was used to synthesize biomimetic poly (2-methacryloyloxyethyl phosphorylcholine)- b -Poly ( n -butyl methacrylate) (PMPC- b -PBMA) nanoparticles which were used as nanocarriers to encapsulate theranostic IR-780 molecules. IR-780 endowed the PMPC- b -PBMA nanoparticles with dual functions including tumor near-infrared (NIR) imaging and photothermal therapy (PTT). The IR-780 encapsulated PMPC- b -PBMA (PMPC- b -PBMA/IR-780) nanoparticles showed good monodispersity and significant stability. The photothermal effects and photothermal cytotoxicity of the PMPC- b -PBMA/IR-780 nanoparticles were studied in vitro . High accumulation of the PMPC- b -PBMA/IR-780 nanoparticles in tumor tissue was verified by whole-animal NIR imaging. The resulted IR-780 encapsulated biomimetic nanoparticles can be an alternative safe theranostic agent for imaging-guided cancer treatment. Graphical abstract: Highlights: Theranostic nanoparticles were easily obtained by miniemulsion polymerization. The as-prepared nanoparticles showed good monodispersity and significant stability. The nanoparticles possessed better photothermal cytotoxicity than free IR-820. The nanoparticles showed better diagnosis effects than free IR-780.